AGILE REQUIREMENTS MANAGEMENT CHALLENGES AND STRATEGIC RECOMMENDATIONS IN INDONESIA’S NATIONAL SINGLE WINDOW - Dencaswo Purnomo; Teguh Raharjo; Ni Wayan Trisnawaty (LPPM Nusa Mandiri, 2026)
Agile methodology is widely adopted by organizations with dynamic user needs, particularly in complex environments involving multiple stakeholders such as ministries and agencies in the public sector. The Indonesia National Single Window Agency (LNSW), which facilitates electronic data exchange for national exports, imports, and logistics, faces this condition. This study aims to identify challenges in requirements management and provide recommendations for LNSW. This study uses three stages: (1) a Systematic Literature Review (SLR) of 15 main articles, (2) validation and categorization of challenges through interviews and questionnaires analyzed using the Content Validity Index (CVI) method (S-CVI/Ave = 1, S-CVI/UA = 1), and (3) development of practical recommendations. This study identifies 12 challenges in the requirements management process at LNSW, which are categorized based on the 4P framework: People (lack of expertise in respective fields, lack of stakeholder problem identification), Process (uncertainty and dynamics of requirements, inability to set requirement priorities, organizational bureaucracy, poor documentation practices), Project (difficulty in estimating time and cost, unrealistic targets, lack of clarity in roles and responsibilities), and Product (lack of product vision, issues in user story development, and technical issues). Based on these challenges, 12 recommendations are proposed, along with operational guidance in the form of an Agile Requirements Playbook tailored for public sector organizations with multi-stakeholder environments. This study contributes to both theory and practice by providing a context-specific Agile Requirements Playbook with validated recommendations to support requirements management in complex public sector environments.